Promoting Students’ Accuracy in Pronouncing Consonant Sounds by Using English Pronunciation Software - Muhammad Sifaul Ulum Harlika; Muhammad Saifuddin; Nailul Fauziyah (Journal of Research in Foreign Language Teaching (JRFLT), 2018)
Good pronunciation accuracy is an essential aspect to be able to speak English well. This research aimed to improve the students’ accuracy in pronouncing consonant sounds at Class XI Ak-1 of SMKN Mojoagung. This research used Classroom Action Research as the research design. The result showed that there were 74% of 35 students passed the passing grade, while the criteria of success in this research was 70%. It meant that the cycle stopped, and the action was succesfully done. It could be concluded that the use of the software could improve students pronunciation accuracy especially in pronouncing consonant sounds by utilizing more the features in the software that showed manner of articulation and voicing before explaining the theory specifically, and giving more practices during the teaching and learning process.